Plastics Technical Services laboratory at Dow Chemical Company - Dow Chemical Company (1952)
General view of an unidentified employee conducting low-temperature research in the Dow Chemical Company's Plastics Technical Services laboratory. In the chemical industry, a variety of machines and apparatus are commonly used to expose products to environmental conditions, such as cold or humidity, in order to test their durability and weather-resistance.
Keywords: Employees; Scientific apparatus and instruments; Research, Industrial; Dow Chemical Company; Quality control; Research, Industrial--Laboratories; Laboratories